COVID-19 DAN IMPLIKASI BAGI USAHA KECIL MENENGAH (Studi Kasus Kelurahan Landungsari, Jawa Timur) - Bulu, Oktaviana Azuba Loru; Suhendri, Hendrik; Indah, Sri (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2023)
One of the business sector in Indonesia is Small and Medium Enterprises (UKM), which have an important role for economic growth, but for now, small, and medium enterprises are one of the businesses that have collapsed due to a decrease in income due to the Covid-19 pandemic. This study aims to determine whether there is a difference in income after and when Covid-19 occurs in, small and medium enterprises (UKM). The method used in this research is quantitative research methods and different tests. In this research, it was obtained by collecting questionnaires. The population in this study was not known how many, so the researcher used the Non Probability Sampling technique. The researcher used the accidental sampling method, the number of samples. Obtained as many as 31 UKM. Based on the results oh the different test, it obtained a significance value of 0,002<0,05 so that the Covid-19 variabel (X) had a positive effect on the income variabel (Y), which stated that the results of tcount were greater than, namely 3,439(X), 4,689(Y) > 1,468 means ho is rejected and is accepted. The decline in income in small and medium enterprises (UKM) in Landungsari Vilage and how to take emergency measuresto help Small and Medium Enterprises to survive the condition of the covid-19 pandemic.